A Novel Hybrid Digital Image Encryption Technique - Thada, Vikas; Shrivastava, Utpal (International Journal of Computer Sciences and Engineering, 2025)
In this growing era of information technology and the Internet, everybody is using interactive media in communication directly or indirectly. Images may have high confidential data.So these images need high security when they are stored somewhere, and when there is a need to send over any insecure communication network, then it is required to provide complete protection from tampering, accessing by illegal party that is not intended receiver. In this research work the problem is to design a novel scheme for 2D image encryption and decryption using an affine cipher, circular rotation of image matrix and the XOR operation. Father the security is enhanced by the fact that main secret key is broken into 3 sub keys and same sub keys are used for encrypting the three different panels of an RGB image. The use of circular shift is also performed by applying a secret operation on a secret key. A special secret key was also generated to be applied during the XOR operation after affine transformation is performed on the original. The cumulative effect of all the above steps results in secure encryption of the image. The encryption process is written in such a manner so that it can be easily reversed and decryption can be achieved by simply running the encryption algorithm in reverse order. This proposed encryption scheme can efficiently be utilized for securing the digital images.